Test on the Stabilization of Oil-Contaminated Wenzhou Clay by Cement. (12th July 2018) - Yu, Chuang; Liao, Raoping; Zhu, Chaopeng; Cai, Xiaoqing; Ma, Jianjun
Abstract : Oil-contaminated soils have been paid much attention due to the reclamation of industrial lands in coastal cities of China. As known, oil-contaminated soils are inapplicable for construction due to their weak engineering properties, thus leading to the requirement of remediation and reclamation for oil-contaminated sites. This study presents an experimental investigation on the stabilization of contaminated soils with Portland cement. Investigations including the Atterberg limits, unconfined compressive strength, direct shear strength, and microstructure of cement-stabilized soils have been carried out, verifying the suitability of applying cement to improve engineering properties. Experimental results show that the geotechnical properties of contaminated soil are very poor. With the application of cement, the liquid limit and plasticity index of contaminated soil samples decrease dramatically, and the strength of treated soils has been improved. Experimental results from scanning electron microscope (SEM) indicate that cement-stabilized oil-contaminated soil is featured with a stable supporting microstructure, owing to the cementation between soil particles. This also confirms the applicability of cement to be served as an additive to treat oil-contaminated soils.